Circulating Inflamma-miRs as Potential Biomarkers of Cognitive Impairment in Patients Affected by Alzheimer’s Disease - Giuliani, Angelica; Gaetani, Simona; Sorgentoni, Giulia; Agarbati, Silvia; Laggetta, Maristella; Matacchione, Giulia; Gobbi, Mirko; Rossi, Tommaso; Galeazzi, Roberta; Piccinini, Gina; Pelliccioni, Giuseppe; Bonfigli, Anna Rita; et al. (Frontiers in Aging Neuroscience, 2021)
Alzheimer’s disease (AD), the most prevalent neurodegenerative disease in the growing population of elderly people, is still lacking minimally-invasive circulating biomarkers that could facilitate the diagnosis and the monitoring of disease progression. MicroRNAs (miRNAs) are emerging as tissue-specific and/or circulating biomarkers of several age-related diseases, but evidence on AD is still not conclusive. Since a systemic pro-inflammatory status was associated with an increased risk of AD development and progression, we focused our investigation on a subset of miRNAs modulating the inflammatory process, namely inflamma-miRNAs. The expression of inflamma-miR-17-5p, -21-5p, -126-3p, and -146a-5p was analyzed in plasma samples from 116 patients with AD compared with 41 age-matched healthy control (HC) subjects. MiR-17-5p, miR-21-5p, and miR-126-3p plasma levels were significantly increased in AD patients compared to HC. Importantly, a strong inverse relationship was observed between miR-21-5p and miR-126-3p, and the cognitive impairment, assessed by Mini-Mental State Examination (MMSE). Notably, miR-126-3p was able to discriminate between mild and severe cognitive impairment. Overall, our results reinforce the hypothesis that circulating inflamma-miRNAs could be assessed as minimally invasive tools associated with the development and progression of cognitive impairment in AD.